The effect of COVID-19 vaccination on the menstrual cycle in female in Riyadh, Saudi Arabia - Hayat Saleh Alzahrani; Saba Ali Algashami; Alanoud Abdulaziz Alharkan; Noura Sultan Alotaibi; Naelah Waseem Algahs (Elsevier, 2023)
Background: Recently, few studies have mentioned minor changes in women's menstrual cycle after the COVID-19 vaccination. There were many reported cases of female menstrual cycle problems in primary healthcare clinics in Riyadh, Saudi Arabia. The study aimed to explore the prevalence of menstrual irregularities after the COVID-19 vaccine among females of childbearing age in Riyadh, Saudi Arabia. Materials and Methods: This observational cross-sectional study was conducted from dec 2021 to June 2022 in Saudi Arabia. The study was carried out by using a convenience sampling technique. Results: Our analysis includes 1066 participants. Abnormal menstruation was significantly associated with hypertension (p-value = 0.024), polycystic ovary syndrome (p-value = 0.001), and at least one gynaecological condition (p-value < 0.001). However, the multivariate regression analysis showed that menstrual abnormality before receiving the COVID-19 vaccine (OR = 0.09, 95% CI, 0.06 to 0.14, p-value < 0.001) was more likely to be associated with abnormal menstruation after receiving the vaccine. Conclusions: Our study findings showed a significant association between covid-19 vaccination and menstruation irregularity before administering the covid-19 vaccine, irrespective of vaccine type or the number of doses administered. Future and ongoing clinical trials should investigate menstrual abnormalities, other abnormal vaginal bleeding and hormonal changes post-vaccination, especially the COVID-19 vaccine.